2019
DOI: 10.1002/jmri.26771
|View full text |Cite
|
Sign up to set email alerts
|

Status of growth plates can be monitored by MRI

Abstract: Background: Growth plate injuries and disorders cause premature closure, resulting in shortened or deformed limbs. Quantitative assessment by MRI might monitor the status of the growth plate and may assist in the prediction of these deformations. Purpose: To investigate whether the status of the growth plate can be monitored by quantitative evaluation using MRI of the noninjured region of the growth plate in a physeal injury model. Study Type: Prospective, longitudinal. Animal Model: A 3.0-mm drill was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…We used a multi‐gradient echo 3D sequence to assess growth plate height and volume and found that it performed equal to the other modalities. Our study supports the findings of Wada et al who used Japanese white rabbits to evaluate the tibial growth plate after physeal injuries using PD‐weighted sequences 27 . Additionally, we observed a correlation of height measurements between MRI using multi‐gradient echo 3D sequence and histomorphometry.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We used a multi‐gradient echo 3D sequence to assess growth plate height and volume and found that it performed equal to the other modalities. Our study supports the findings of Wada et al who used Japanese white rabbits to evaluate the tibial growth plate after physeal injuries using PD‐weighted sequences 27 . Additionally, we observed a correlation of height measurements between MRI using multi‐gradient echo 3D sequence and histomorphometry.…”
Section: Discussionsupporting
confidence: 91%
“…Our study supports the findings of Wada et al who used Japanese white rabbits to evaluate the tibial growth plate after physeal injuries using PD‐weighted sequences. 27 Additionally, we observed a correlation of height measurements between MRI using multi‐gradient echo 3D sequence and histomorphometry. Moreover, our study reports a similar correlation with μCT.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, the monitoring of rickets healing using RSS and radiographs becomes less sensitive in children >13 years old or once growth plate closure has occurred ( 28 , 41 , 42 ). MRI could be helpful to determine closure of growth plates in adolescents and to monitor changes in bone quality ( 43 , 44 ). Additional tools such as EOS 2D/3D imaging and Gait lab could be useful to determine changes in bone quality and bone deformity, especially in older children ( 4 , 45 ).…”
Section: Discussionmentioning
confidence: 99%